Towards a Sustainable Future - Life Cycle Management Challenges and Prospects - Klos, Zbigniew Stanislaw; Kalkowska, Joanna; Kasprzak, Jędrzej (Springer International Publishing : Imprint: Springer, 2022)
This open access book includes a selection of contributions from the Life Cycle Management 2019 Conference (LCM) held in Poznań, Poland, and presents different examples of scientific and practical contributions, showing an incorporation of life cycle approach into the decision processes on strategic and operational level. Special attention is drawn to applications of LCM to target, organize, analyze and manage product-related information and activities towards continuous improvement, along the different products life cycle. The selection of case studies presents LCM as a business management approach that can be used by all types of businesses and organizations in order to improve their sustainability performance. This book provides a cross-sectoral, current picture of LCM issues. The structure of the book is based on five-theme lines. The themes represent different objects that are focused on sustainability and LCM practices mainly related to: products, technologies, organizations, markets and policy issues as well as methodological solutions. The book brings together presentations from the world of science and the world of enterprises as well as institutions supporting economic development.